2022
DOI: 10.3390/jcm11102733
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D3 as an Independent Predicting Marker for One-Year Mortality in Patients with Acute Heart Failure

Abstract: Background: Deficiency in vitamin D3 and its metabolites has been linked to dismal outcomes in patients with chronic diseases, including cardiovascular disease and heart failure (HF). It remains unclear if a vitamin D3 status is a prognostic feature in patients with acute decompensated HF. Methods: We assessed serum levels of 25-OH-vitamin D3 and 1,25-(OH)2-vitamin D3 in 139 patients with acute HF who had been admitted to the intermediate care unit of a maximum care hospital. The follow-up period was one year.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Many observational studies emphasize the association between 25(OH)D levels and cardiovascular disease, atherosclerosis, hypertension and heart disease in CKD patients and the elderly [ 145 ]. Vitamin D deficiency was an independent predictor of mortality in patients with or without heart failure [ 146 , 147 , 148 , 149 ]. It was suggested that seasonal fluctuations in mortality (i.e., decreased CVD-related deaths in the summer and increased deaths in the winter) might be related to the lower vitamin D levels in the blood during winter [ 150 ].…”
Section: Vitamin D Aging and Ckdmentioning
confidence: 99%
“…Many observational studies emphasize the association between 25(OH)D levels and cardiovascular disease, atherosclerosis, hypertension and heart disease in CKD patients and the elderly [ 145 ]. Vitamin D deficiency was an independent predictor of mortality in patients with or without heart failure [ 146 , 147 , 148 , 149 ]. It was suggested that seasonal fluctuations in mortality (i.e., decreased CVD-related deaths in the summer and increased deaths in the winter) might be related to the lower vitamin D levels in the blood during winter [ 150 ].…”
Section: Vitamin D Aging and Ckdmentioning
confidence: 99%
“…Thus, we suggest that the authors of Ref. [ 1 ] reanalyze the results of their study in terms of PTH rather than only 25(OH)D concentrations. PTH (parathormone) concentrations are reported in Table 1 (36.50 ± 29.64 pg/mL).…”
mentioning
confidence: 99%
“…The communication by Thiele et al reported that there were no significant differences in serum 25-hydroxyvitamin D (25(OH)D) for the 22 of 118 acute heart failure (HF) patients, 71% with de novo HF and 29% with chronic HF, who died within 12 months after admission to the intermediate care unit of a maximum care hospital in Germany compared to those who survived [ 1 ]. The authors noted that this outcome differed from what was expected from the Seattle Heart Failure Model [ 2 ].…”
mentioning
confidence: 99%